City Transport Monitoring and Routes Management System - Dagockis, M.; Daunoras, J.; Bagdonas, V. (Elektronika ir Elektrotechnika, 2009)
The article analyzes a problem of further development of traffic control informational systems in order to present to the road users effective information about the shortest in respect of time routes and thus to improve use of existing city transport infrastructure. To solve this task it is suggested to create dynamic (automatically updated in real time) street passing durations base, for support of which a city transport monitoring system operating in real time is necessary consisting of a network of sensors, a data collection communications system and a data processing system. In the article it is shown that to predict a street passing duration it is necessary to measure speed and traffic density in the characteristic points of the street. Measurements of do not significantly improve accuracy of forecast of a street passing time. Methodology are presented meant to forecast a street passing time. Ill. 2, bibl. 4 (in English; summaries in English, Russian and Lithuanian).